Exploring the psychological mechanisms behind consumption patterns and their effect on economic expansion - Yujie Liu; Nelli Akylbekova; Kalybek Abdykadyrov (Environment and Social Psychology, 2025)
This study investigates the psychological mechanisms driving consumption patterns and their subsequent impact on regional economic expansion. Drawing on a cross-sectional quantitative design, data were collected from 2,847 participants across six regions using a mixed-mode approach combining online surveys and structured interviews. A comprehensive analytical framework was developed to examine how cognitive biases, financial literacy, and digital literacy collectively influence consumption behaviors such as green consumption, impulsive buying, and planned purchases, and how these patterns contribute to macroeconomic performance. Using structural equation modeling (SEM), the proposed model demonstrated a strong fit (χ²/df = 2.14, CFI = 0.962, TLI = 0.955, RMSEA = 0.041). Results revealed that financial literacy positively predicted planned purchases (β = 0.42, p < 0.001) and green consumption (β = 0.35, p < 0.001) while negatively influencing impulsive buying (β = −0.28, p < 0.01). Cognitive biases significantly mediated the relationship between financial literacy and consumption behaviors, explaining 31.4% of indirect effects. In addition, the rational decision making and reduction in impulsiveness by digital literacy mediated the impact of these associations. Taken together, psychological mechanisms correlated to 34.2 percent of the variance of consumption patterns, which, in its turn, explained 28.7 percent of the changes in regional economic growth. Its results focus on the final contribution of consumer psychology to economic performance and give additional results concerning the improvement of financial literacy programs, online consumer protection, and sustainable marketing. This research paper adds to the body of behavioral economics by incorporating the three aspects of psychology, technology and financial in one model that predicts the psychology economic nexus.